Economic theory and development options for the Caribbean : the Sir Arthur Lewis Memorial Lectures 1996-2005 - Lewis, W. Arthur; Gonsalves, Ralph; Venner, Dwight; Eastern Caribbean Central Bank. (Kingston: Ian Randle Publishers, 2007)
Reflects the ethos of Lewis's approach to development and the utility of economics as a problem solving discipline.
Includes bibliographical references and index.
Keywords: Lewis, W. Arthur; Economic development -- Caribbean Area; Economic conditions -- Caribbean Area